Abdominal tuberculosis masquerading as ovarian carcinoma in a Caucasian woman: a diagnostic challenge. Issue 2 (25th February 2022) - Das, Ananya; Mead, Paul; Mala, Hilal Razvi
Abstract : We present a case of a 37-year-old Caucasian woman with abdominal distension and loss of weight. She was initially presumed to be a case of ovarian malignancy due to an elevated serum cancer antigen 125 (CA 125) level and imaging of abdomen and pelvis that showed ascites and bulky ovaries. However, histological examination of biopsy later revealed it to be a case of abdominal tuberculosis (AbT). Ascitic fluid was also found to be positive for Mycobacterium tuberculosis by whole genome sequencing. The patient was started on antituberculosis treatment following which she showed a significant improvement in her symptoms.